Electroactive soft actuators utilizing PEDOT:PSS and 3D lithium-ion-conducting phosphate columnar liquid crystals embedded in a porous polyethylene membrane - Chengyang Liu; Masafumi Yoshio (Science and Technology of Advanced Materials)
This study introduces a novel supramolecular thermotropic columnar liquid-crystalline (LC) electrolyte tailored for high-performance ionic electroactive polymer (iEAP) actuators. The electrolyte is designed by integrating lithium salts into a taper-shaped molecule with bisphosphate moieties (BPO), which self-assembles into a columnar hexagonal (Colh) phase, forming 3D continuous ion-conductive pathways. This architecture achieves high ionic conductivity of up to 2 × 10−4 S cm−1 at room temperature. An actuator was fabricated by embedding this electrolyte into a microporous polyethylene membrane, sandwiched between PEDOT:PSS electrodes. The resulting device exhibits exceptional performance, achieving a bending strain of 0.52% and a force output of 0.5 mN under a ± 2 V, along with outstanding durability, retaining its performance over 9000 cycles. These results underscore the potential of 3D ion-conductive LC electrolytes in advancing iEAP actuator technologies, paving the way for innovative applications in tactile interfaces and soft robotics.